Firm Readiness Level for Innovation Projects: A New Decision-Making Tool for Innovation Managers - Galvez-Manriquez, D (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
Innovation projects represent a major challenge for business managers due to their associated uncertainty degree. The already existing methodologies to support the innovation projects are aimed at piloting them and establishing the management stages in a flexible and agile way during their deployment. This paper proposes a complementary ex-ante methodology that seeks to aid the decision-making of companies to choose whether or not to launch a potential innovation project. This methodology evaluates to what extent the technological system of the company has the minimum required maturity degree of competencies to successfully achieve the innovation project. Thus, in first instance, an innovation project is characterized according to its novelty degree; both inside the company and in its environment. Subsequently, according to the previous characterization, the future project will have an impact on the technological system of the company. The capabilities of the firm are represented by a set of good practices associated with the innovation projects’ management that the company is able to deploy. Finally, the minimum maturity degree required by a particular project of these practices is determined. Then, the gap between the maturity requirement profile and the current profile of the company is established enabling to decide on the implementation of the project or not. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.